K-Shell Ionization Cross Sections of Light Atoms Due to Electron Impact (Journal of Atomic and Molecular Sciences, 2021)
Electron impact ionization cross sections (EIICS) of K-shell have been evaluated for light atoms (C, N, O) at incident energies ranging from ionization threshold to 1 GeV. The plane wave Born approximation is used in the proposed model by incorporating it in exchange, coulomb and relativistic effects along with the contributions of transverse interaction to ionization cross sections. In present model, we require two constants for each atom, ionization energy $(I)$ and the electron occupation number $(N).$ Adequate comparisons have been made with other theoretical methods, empirical formulae. The predicted EIICS of K-shell also compared with experimental data. Obtained results are in good agreements with available experimental data.
Keywords: ionization cross section; electron impact; K-shell.